ETV4 is a theranostic target in clear cell renal cell carcinoma that promotes metastasis by activating the pro-metastatic gene FOSL1 in a PI3K-AKT dependent manner. (10th July 2020) - Xu, Liang; Hu, Hao; Zheng, Li-Sheng; Wang, Meng-Yao; Mei, Yan; Peng, Li-Xia; Qiang, Yuan-Yuan; Li, Chang-Zhi; Meng, Dong-Fang; Wang, Ming-Dian; Liu, Zhi-Jie; Li, Xin-Jian; et al.
Abstract: Distant metastasis is the major cause of short survival in ccRCC patients. However, the development of effective therapies for metastatic ccRCC is limited. Herein, we reported that ETV4 was selected from among 150 relevant genes with in vivo evidence of promoting metastasis. In this study, we identified that ETV4 promoted ccRCC cell migration and metastasis in vitro and in vivo, and a positive correlation between ETV4 and FOSL1 expression was found in ccRCC tissues and cell lines. Further investigation suggested that ETV4 increase FOSL1 expression through direct binding with the FOSL1 promoter. Furthermore, ETV4/FOSL1 was proved as a novel upstream and downstream causal relationship in ccRCC in an AKT dependent manner. In addition, both ETV4 and FOSL1 serve as an independent, unfavorable ccRCC prognostic indicator, and the accumulation of the ETV4 and FOSL1 in ccRCC patients result in a worse survival outcome in ccRCC patients. Taken together, our results suggest that the ETV4/FOSL1 axis acts as a prognostic biomarker and ETV4 directly up-regulates FOSL1 by binding with its promoter in a PI3K-AKT dependent manner, leading to metastasis and disease progression of ccRCC. Highlights: We have demonstrated for the first time that ETV4 is a key player in ccRCC metastasis. We found that elevated ETV4 and FOSL1 expression in ccRCC were both independent unfavorable prognostic factors for OS. We found that the ETV4/FOSL1 axis maintains the ability of metastasis in a PI3K-AKT dependent manner. We found that ETV4/FOSL1 axis may be valuable to develop new strategies for treating ccRCC patients with metastasis.